Atomic Layer Deposition of SnO2-Based Composite Anodes for Thin-Film Lithium-Ion Batteries - Zhao, Bo; Dhara, Arpan; Dendooven, Jolien; Detavernier, Christophe (Frontiers in Energy Research, 2020)
Transition metal oxides are promising anode materials for lithium-ion batteries thanks to their good electrochemical reversibility, high theoretical capacities, high abundance, and low cost. The mechanism of lithium insertion or deintercalation into or from these metal oxides can be different depending upon their lattice structure or chemical nature. Synergistic effects obtained from mixing different metal oxides with (dis)similar lithiation/delithiation mechanisms (intercalation, conversion and alloying) can significantly improve the device performances. In this research, we systematically investigate the impact on electrochemical properties of SnO2 thin-films upon mixing with TiO2, Fe2O3 and ZnO. In these pure thin-films, SnO2 displays conversion- as well as alloying-type lithiation and serves as the host material, whereas TiO2 represents an intercalation-type anode material, Fe2O3 exhibits conversion reactions and ZnO expresses alloying during lithiation-delithiation processes. Importantly, all the composite thin-films have an intermixed structure at the atomic scale, as they are precisely prepared by the atomic layer deposition method. The electrochemical properties demonstrate that the composite thin-films show better performance, either higher capacities or better cycling retentions, than the individual constituent material (SnO2, TiO2, Fe2O3 or ZnO). Overall cycling stability improves to a great extent along with a slight increase in capacity with the addition of TiO2. The supplement of Fe2O3 in the SnO2–Fe2O3 composite thin-films moderately improves both capacity and retention, while the SnO2–ZnO composite electrodes demonstrate a good cyclability and stabilize at a relatively high capacity. The systematic investigation of synergistic effects on the different types (intercalation, conversion and alloying) of metal oxide composites is expected to provide guidance towards the development of composite anode materials for lithium-ion batteries.